Métodos de resolução para as equações quadráticas - PINHEIRO, João Batista Santana (2024)
This work highlights the importance of quadratic functions and second equations degree for the development of mathematical thinking and the systematic resolution of problems. Explores its practical applications in areas such as physics, engineering, economics, natural sciences and computing, including the modeling of real-world phenomena and optimization of business costs. Furthermore, it emphasizes that understanding these equations is essential for understanding advanced mathematical concepts, such as exponential and logarithmic functions, differential and integral calculus, and analytical geometry. O Studying these concepts also promotes fundamental skills such as critical analysis, problem solving, and logical and abstract thinking, relevant in several areas professionals and academics.